Tom, volume e arranjo no chiaroscuro da memória: Sinfonia em branco, de Adriana Lisboa - Regina R. Félix (Estudos de Literatura Brasileira Contemporânea)
This article shows the parallel between the psychological process of the characters Tomás, Maria Inês and Clarice and the musical, plastic, cinematographic, and literary forms through which they express their gradual awareness in dealing with their traumas. Tone, volume, and arrangement merge with each other. They are configured as appearance and absence, in shadow and light, and in voices that modulate silences and protests. The characters’ memories, disconnected and repetitive, are orchestrated according those aesthetic patterns as an attempt to unravel the absurdity of their situation.